Penerapan Model Active Learning Tipe True or False untuk Meningkatkan Minat Belajar Siswa - Kristanti, Ningsih (Global Journal Teaching Professional, 2023)
This research activity motivated by the low interest in learning for fourth grade students at UPTD SDN 183 Buyuntana. This study aims to increase interest in learning through the application of the true or false model for fourth grade students at UPTD SDN 183 Buyuntana, which is carried out for 2 cycles with 2 meetings in each cycle. The subjects in this study were fourth grade students at UPTD SDN 183 Buyuntana. The number of students is 28 students. The form of research is classroom action research. The research instrument consisted of learning interest instruments and data collection instruments in the form of teacher activity observation sheets. Based on the research, the application of this model can increase the learning interest of fourth grade students at UPTD SDN 183 Buyuntana. Teacher activity in cycle I got the proportion of 94.115 in the very good category while in cycle II it got the proportion of 97.78% in the very good category. Student interest in cycle I got an average of 52.37% in the less category while in cycle II got an average of 85.71% in the very good category. In cycle I it has not been said to be complete while in cycle II the research has been completed or is interested in an interest indicator of 100% exceeding the predetermined performance indicator of 75%. Kegiatan penelitian ini dilatarbelakangi oleh rendahnya minat belajar siswa kelas IV di UPTD SDN 183 Buyuntana. Penelitian ini bertujuan untuk meningkatkan minat belajar melalui penerapan model true or false siswa kelas IV di UPTD SDN 183 Buyuntana, yang dilaksanakan selama 2 siklus dengan 2 kali pertemuan di setiap siklusnya. Sebagai Subjek dalam Penelitian ini adalah siswa kelas IV di UPTD SDN 183 Buyuntana. Jumlah siswa sebanyak 28 orang siswa. Bentuk penelitian adalah penelitian tindakan kelas. Instrumen penelitian ini terdiri dari instrumen minat belajar dan instrumen pengumpulan data berupa lembar observasi aktivitas guru. Berdasarkan penelitian yang dituangkan pada pembahasan, penerapan model True or False dapat meningkatkan minat belajar siswa kelas IV di UPTD SDN 183 Buyuntana. Aktivitas guru pada siklus I mendapat persentase 94,115 dengan kategori sangat baik sedangkan pada siklus II mendapat persentase 97,78 % dengan kategori sangat baik. Minat belajar siswa pada siklus I mendapat rata-rata 52,37 % dengan kategori kurang sedangkan pada siklus II mendapat rata-rata 85,71 % dengan kategori sangat baik. Pada siklus I ini belum dikatakan tuntas sedangkan pada siklus II penelitian telah tuntas atau berminat dengan indikator keberminatan 100% melebihi indikator kinerja yang telah ditetapkan yaitu 75%.